Analiasis Yuridis Terhadap Tindak Pidana Pengelolaan Limbah B3 Tanpa Izin (Studi Putusan No. 2132K/Pid.Sus-LH/2016) - Maria Theresia Tarigan; Andy Putra Namo; Ghaniu Rezya Pratama; Sigar P. Berutu; Andi Hakim Lubis (Universitas Batanghari Jambi, 2023)
The purpose of this study was to learn more about the legislative framework governing the disposal of toxic and hazardous waste, as well as how the panel of judges views the imposition of sanctions in decision No. 2132 K/Pid.Sus-LH/2016. The research was normative juridical law research with the goal of describing or investigating legal concerns derived from documentation studies through literature analysis, data processing from primary, secondary, and tertiary legal sources, and literature study. Law No. 32 of 2009 concerning environmental protection and management and PP No. 22 of 2021 concerning the implementation and management of the environment, which replaces PP No. 101 of 2014 concerning Hazardous and Toxic Waste Management, are the regulations for criminal acts for the management of hazardous and toxic waste (B3) that are applicable in Indonesia. In Decision No. 2132K/Pid.Sus-LH/2016, the judge at the cassation level rejected the Defendant's request for a cassation on the grounds that Judex Facti had not applied the law incorrectly and had tried the Defendant in accordance with the relevant procedural law and had not overstepped his bounds. This case involved B3 waste management without a permit.